Electrolyte for improving performance of zinc-halogen battery and preparation method thereof
By using an electrolyte containing 1-propyl-3-methylimidazole bromine salt in zinc-halogen batteries, the problem of slow iodine conversion kinetics and dendrite in zinc-halogen batteries was solved, and a higher energy density was achieved and cycle life.
Patent Information
- Application Number
- CN202411442486.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-24
AI Technical Summary
In practical applications, existing zinc-halogen batteries have problems with slow iodine conversion kinetics, multi-iodide dissolution shuttle effect and zinc negative dendrite, which limits the energy density and cycle life of the battery.
Using an electrolyte including ionic liquid and zinc salt, the addition of 1-propyl-3-methylimidazole bromine salt to zinc salt and deionized water can promote the uniform deposition of zinc ions and the regular conversion of iodine, and inhibit the branches. Crystal growth activates the redox reaction of iodine.
The energy density and cycle life of zinc-halogen batteries are improved, and the regular conversion of iodine is activated through catalytic action, uniform deposition is promoted, tip effect and dissolution shuttle of polyiodide are inhibited, and the application prospects of batteries are enhanced.
Smart Images

Figure CN119181850A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to an electrolyte for improving the performance of a zinc-halogen battery and a preparation method thereof. Background Art
[0002] As a widely used energy storage device, lithium-ion batteries face many limitations. First, the scarcity of lithium resources and their large consumption have limited their total production capacity, and the cost of raw materials for lithium batteries remains high. Second, electrolytes and battery materials are highly toxic. Once leaked, they will not only pollute the environment, but also endanger human health, which makes the production conditions of lithium batteries extremely harsh. In addition, the news of short circuits and spontaneous combustion of electric vehicle batteries in recent years has also had a negative impact on the development of lithium-ion batteries. Therefore, the development of highly safe, green, low-cost and high-energy-density secondary batteries has become one of the key challenges in the current new energy field.
[0003] In contrast, the zinc metal negative electrode has a lower redox potential and a higher theoretical capacity, which can achieve a higher energy density. In addition, aqueous zinc secondary batteries use aqueous electrolytes, which have the advantages of high safety, green environmental protection, and easy handling. Therefore, high-energy-density aqueous zinc secondary batteries have broad application prospects in the field of electrochemical energy storage in the future. The low solubility of iodine in water makes it suitable for aqueous batteries. Unlike traditional zinc batteries that rely on the insertion and extraction of zinc ions, aqueous zinc-iodine batteries achieve energy storage through the redox reaction of iodine and the deposition / stripping of zinc. The redox reaction of iodine can provide a higher discharge voltage and high theoretical capacity in aqueous zinc-based batteries. In addition, the multiple valence states of iodine theoretically give it the potential for multi-electron conversion reactions. In recent years, zinc-iodine batteries have made significant progress in the development of high-specific capacity and long-life positive electrode materials, involving carbon materials, single-atom materials, coordination materials, and conductive polymers. In terms of zinc negative electrodes, related research mainly focuses on inhibiting dendrite growth, reducing byproducts, and preventing polyiodide corrosion.
[0004] A new type of Janus functional binder based on chitosan has been proposed in the prior art. The polar groups in the chitosan molecules have a strong affinity with iodine species, which will also promote the quasi-reduction catalytic conversion rate of iodine and jointly inhibit the shuttle effect. With these advantages, the cycle performance and capacity of zinc-iodine batteries using chitosan binders have been significantly improved. There is also a technical solution that proposes a strategy of introducing heterogeneous halogen iodine bromide into an aqueous electrolyte containing hydrogen ions and bromide ions, which successfully activates the reversible reaction of the twelve-electron redox couple of iodide ions / iodate ions; during the charging process, bromide ions promote the generation of iodine bromide intermediates, which is beneficial to the oxidation process of iodine to iodate ions; during the discharge process, bromine is first reduced to bromide ions, and then hydrogen ions and bromide ions will spontaneously react with bromate ions to generate iodine bromide, which promotes the subsequent reduction of iodine and iodide ions.
[0005] However, existing zinc-halogen batteries face some key challenges in practical applications, such as slow positive ion conversion kinetics, dissolution shuttling effect of multiple iodides and dendrite problem of zinc anode, which limit the energy density and cycle life of the battery.
[0006] Therefore, according to the above-mentioned related technologies, it is urgent to develop an electrolyte and a preparation method thereof for improving the performance of zinc-halogen batteries. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide an electrolyte for improving the performance of zinc-halogen batteries and a preparation method thereof, so as to solve the problem of poor battery energy density and cycle life caused by the electrolyte in zinc-halogen batteries in the prior art.
[0008] Based on the above objectives, the present invention provides an electrolyte for improving the performance of a zinc-halogen battery and a preparation method thereof.
[0009] An electrolyte for improving the performance of a zinc-halogen battery comprises an ionic liquid, a zinc salt and deionized water.
[0010] Preferably, the ionic liquid is any one of 1-ethyl-3-methylimidazolium bromide, 1-propyl-3-methylimidazolium bromide and 1-butyl-3-methylimidazolium bromide.
[0011] Preferably, the ionic liquid is 1-propyl-3-methylimidazolium bromide.
[0012] Preferably, the zinc salt is any one of zinc trifluoromethanesulfonate, zinc sulfate heptahydrate, zinc chloride, zinc acetate, zinc tetrafluoroborate, and zinc perchlorate hexahydrate.
[0013] Preferably, the zinc salt is zinc trifluoromethanesulfonate.
[0014] A method for preparing an electrolyte for improving the performance of a zinc-halogen battery comprises the following steps:
[0015] Step S1. First, add zinc salt to deionized water and stir to obtain a reference electrolyte;
[0016] Step S2. Add ionic liquid to the reference electrolyte and stir to obtain an electrolyte that improves the performance of the zinc-halogen battery.
[0017] Preferably, the mass ratio of the zinc salt to deionized water in step S1 is 11-22:10-20.
[0018] Preferably, the stirring time in step S1 is 10-20 min.
[0019] Preferably, the mass ratio of the reference electrolyte to the ionic liquid in step S2 is 21-22:4-17.
[0020] Preferably, the stirring time in step S2 is 24-25 hours.
[0021] Beneficial effects of the present invention:
[0022] The present invention provides an electrolyte for improving the performance of a zinc-halogen battery and a preparation method thereof. The present invention adopts halogen elements as electron-donating groups to participate in the solvation structure of zinc ions, thereby reducing the free water activity and achieving rapid desolvation; at the same time, since imidazolium cations are preferentially adsorbed on the surface of the zinc anode, the reconstruction of the inner Helmholtz plane is achieved, and the zinc ions are uniformly and densely deposited through steric hindrance and electrostatic synergistic effects, thereby shielding the tip effect and inducing the growth of the Zn (101) dominant crystal plane;
[0023] On the other hand, since the unshared electron pair of the 1-position nitrogen atom of the imidazole ring in the ionic liquid participates in the cyclic conjugation, the electron density of the nitrogen atom is reduced, making it easy for the hydrogen on this nitrogen atom to leave in the form of hydrogen ions; this characteristic enables the imidazole ring to flexibly give or accept protons, thereby having a certain catalytic effect.
[0024] Therefore, compared with the prior art, the electrolyte prepared by the present invention can not only inhibit the growth of zinc negative electrode dendrites, promote uniform deposition, and activate the positive valence conversion of iodine through catalysis, but also realize the regulation of the positive and negative electrodes of the zinc battery, so that it has a broader application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 Cyclic voltammetry curves of zinc-iodine full batteries assembled with the electrolytes prepared in Example 1 and Comparative Example 18 of the present invention;
[0027] Figure 2 Cyclic voltammetry curves of zinc-iodine full batteries assembled with the electrolytes prepared in Example 1, Comparative Example 20 and Comparative Example 6 of the present invention;
[0028] Figure 3 The electrolytes prepared in Example 1, Comparative Example 18 and Comparative Example 19 of the present invention were assembled into symmetrical cells at a current density of 5 mAh·cm -2 , deposition capacity is 1 mAh cm -2 Cycle curve when
[0029] Figure 4 The electrolytes prepared in Example 1, Comparative Example 6, Comparative Example 18 and Comparative Example 20 of the present invention were assembled into zinc-copper half-cells at a current density of 5 mAh·cm -2 , deposition capacity is 1 mAh cm -2 Cycle curve when
[0030] Figure 5 This is a scanning electron microscope photograph of the metal negative electrode after the electrolyte prepared in Example 1 of the present invention is assembled into a symmetrical battery and then cycled for 100 times;
[0031] Figure 6 The X-ray diffraction pattern of the metal negative electrode after the electrolyte prepared in Example 1 of the present invention is assembled into a symmetrical battery and then cycled for 100 times;
[0032] Figure 7 Cycle curves of zinc-iodine full batteries assembled with the electrolytes prepared in Example 1, Comparative Example 18 and Comparative Example 19 of the present invention;
[0033] Figure 8 The charge and discharge curves of the zinc-iodine full battery assembled with the electrolytes prepared in Example 1, Comparative Example 18 and Comparative Example 19 of the present invention;
[0034] Fig. 9 The rate performance curve of the zinc-iodine full battery assembled with the electrolyte prepared in Example 1 of the present invention;
[0035] Fig.10This is a curve of a zinc-iodine full battery with a low N / P ratio assembled using the electrolyte prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0037] The sources and properties of some of the raw materials used in the present invention are as follows:
[0038] 1-Ethyl-3-methylimidazolium bromide was purchased from Wuhan Huajiu Pharmaceutical Technology Co., Ltd., CAS: 65039-08-9, 1-propyl-3-methylimidazolium bromide was purchased from Wuhan Huajiu Pharmaceutical Technology Co., Ltd., CAS: 85100-76-1; 1-butyl-3-methylimidazolium bromide was purchased from Wuhan Huajiu Pharmaceutical Technology Co., Ltd., CAS: 85100-77-2; zinc trifluoromethanesulfonate was purchased from Hubei Shishun Biotechnology Co., Ltd., CAS: 54010-75- 2; zinc sulfate heptahydrate was purchased from Wuhan Haorong Biotechnology Co., Ltd., CAS: 7446-20-0; zinc chloride was purchased from Wuhan Jiyesheng Chemical Co., Ltd., CAS: 7646-85-7; zinc acetate was purchased from Hubei Hengjingrui Chemical Co., Ltd., CAS: 557-34-6; zinc tetrafluoroborate was purchased from Hubei Chengfeng Chemical Co., Ltd., CAS: 138-26-885; zinc perchlorate hexahydrate was purchased from Hubei Yongkuo Technology Co., Ltd., CAS: 10065-64-6.
[0039] Example 1: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0040] S1. Take 11g of zinc trifluoromethanesulfonate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0041] S2. Add 4.1 g of 1-propyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0042] Example 2: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0043] S1. Take 15g of zinc trifluoromethanesulfonate in a beaker, add 13g of deionized water, stir for 13min, and obtain a reference electrolyte;
[0044] S2. Add 8.05 g of 1-propyl-3-methylimidazolium bromide to 21.45 g of the reference electrolyte and stir for 24.3 h to obtain an electrolyte that improves the performance of a zinc-halogen battery;
[0045] Example 3: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0046] S1. Take 18.06 g of zinc trifluoromethanesulfonate in a beaker, add 17 g of deionized water, stir for 17 min, and obtain a reference electrolyte;
[0047] S2. Add 12.17 g of 1-propyl-3-methylimidazolium bromide to 21.83 g of the reference electrolyte and stir for 24.5 h to obtain an electrolyte that improves the performance of a zinc-halogen battery;
[0048] Example 4: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0049] S1. Take 22g of zinc trifluoromethanesulfonate in a beaker, add 19.97g of deionized water, stir for 20min, and obtain a reference electrolyte;
[0050] S2. Add 16.99 g of 1-propyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 25 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0051] Comparative Example 1: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0052] S1. Take 11g of zinc sulfate heptahydrate in a beaker, add 10g of deionized water, and stir for 10min to obtain a reference electrolyte;
[0053] S2. Add 4.07 g of 1-propyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0054] Comparative Example 2: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0055] S1. Take 11g zinc chloride in a beaker, add 10g deionized water, stir for 10min, and obtain a reference electrolyte;
[0056] S2. Add 4.06 g of 1-propyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of a zinc-halogen battery;
[0057] Comparative Example 3: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0058] S1. Take 11g of zinc acetate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0059] S2. Add 4.11 g of 1-propyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0060] Comparative Example 4: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0061] S1. Take 11g of zinc tetrafluoroborate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0062] S2. Add 4 g of 1-propyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0063] Comparative Example 5: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0064] S1. Take 11g of zinc perchlorate hexahydrate in a beaker, add 10g of deionized water, and stir for 10 minutes to obtain a reference electrolyte;
[0065] S2. Add 4 g of 1-propyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0066] Comparative Example 6: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0067] S1. Take 11g of zinc trifluoromethanesulfonate in a beaker, add 10g of deionized water, and stir for 10min to obtain a reference electrolyte;
[0068] S2. Add 4.32 g of 1-ethyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0069] Comparative Example 7: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0070] S1. Take 11g of zinc trifluoromethanesulfonate, zinc sulfate heptahydrate, zinc chloride, zinc acetate, zinc tetrafluoroborate, and zinc perchlorate hexahydrate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0071] S2. Add 4.11 g of 1-butyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of a zinc-halogen battery;
[0072] Comparative Example 8: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0073] S1. Take 11g of zinc sulfate heptahydrate in a beaker, add 10g of deionized water, and stir for 10min to obtain a reference electrolyte;
[0074] S2. Add 4.1 g of 1-ethyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0075] Comparative Example 9: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0076] S1. Take 11g of zinc sulfate heptahydrate in a beaker, add 10g of deionized water, and stir for 10min to obtain a reference electrolyte;
[0077] S2. Add 4.2 g of 1-butyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of a zinc-halogen battery;
[0078] Comparative Example 10: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0079] S1. Take 11g zinc chloride in a beaker, add 10g deionized water, stir for 10min, and obtain a reference electrolyte;
[0080] S2. Add 4.1 g of 1-ethyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0081] Comparative Example 11: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0082] S1. Take 11g zinc chloride in a beaker, add 10g deionized water, stir for 10min, and obtain a reference electrolyte;
[0083] S2. Add 4.11 g of 1-butyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of a zinc-halogen battery;
[0084] Comparative Example 12: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0085] S1. Take 11g of zinc acetate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0086] S2. Add 4.1 g of 1-ethyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0087] Comparative Example 13: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0088] S1. Take 11g of zinc acetate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0089] S2. Add 4.11 g of 1-butyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0090] Comparative Example 14: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0091] S1. Take 11g of zinc tetrafluoroborate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0092] S2. Add 4.1 g of 1-ethyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0093] Comparative Example 15: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0094] S1. Take 11g of zinc tetrafluoroborate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0095] S2. Add 4.11 g of 1-butyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0096] Comparative Example 16: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0097] S1. Take 11g of zinc perchlorate hexahydrate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0098] S2. Add 4.1 g of 1-ethyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0099] Comparative Example 17: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0100] S1. Take 11g of zinc perchlorate hexahydrate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0101] S2. Add 4.11 g of 1-butyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0102] Comparative Example 18: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0103] S1. Take 11g of zinc trifluoromethanesulfonate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0104] S2. Add 2.3 g of zinc bromide to 21 g of the reference electrolyte and stir for 24 h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0105] Comparative Example 19: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0106] S1. Take 11g of zinc trifluoromethanesulfonate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0107] S2. Add 2g of 1-propyl-3-methylimidazolium bromide to 21g of the reference electrolyte and stir for 24h to obtain an electrolyte that improves the performance of zinc-halogen batteries;
[0108] Comparative Example 20: A method for preparing an electrolyte for improving the performance of a zinc-halogen battery:
[0109] S1. Take 11g of zinc trifluoromethanesulfonate in a beaker, add 10g of deionized water, stir for 10min, and obtain a reference electrolyte;
[0110] S2. Add 2.98 g of 1-ethyl-3-methylimidazolium bromide to 21 g of the reference electrolyte and stir for 24 hours to obtain an electrolyte that improves the performance of the zinc-halogen battery.
[0111] Electrochemical performance testing and data analysis:
[0112] Zinc ion batteries were assembled using the electrolytes for improving the performance of zinc-halogen batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 20. Electrochemical performance tests were performed on the assembled zinc ion batteries. The test results were collated to obtain Figure 1-Figure 10 ; Among them, the electrolytes of Example 1, Comparative Example 18 and Comparative Example 19 were assembled into zinc symmetrical batteries, and the charge and discharge performance tests were carried out. The cycle time was as follows:
[0113] Table 1
[0114] Electrolyte Cycle time (h) Example 1 1100 Comparative Example 18 220 Comparative Example 19 310
[0115] Combined with Table 1 Figure 3 It can be seen that the addition of 1-propyl-3-methylimidazolium bromide ionic liquid has a significant effect on extending the cycle life of the zinc symmetric battery. By comparing Example 1 and Comparative Example 19, it can be seen that different concentrations of ionic liquids also have a certain effect on the cycle life of the battery. By comparison, it can be seen that Example 1 is preferred.
[0116] The electrolytes of Example 1, Comparative Example 6, Comparative Example 18 and Comparative Example 20 were assembled into zinc-copper half-cells, and the charge and discharge performance tests were carried out. The results are as follows:
[0117] Table 2
[0118] Electrolyte Number of cycles Average Coulombic efficiency % Example 1 5000 99.9 Comparative Example 6 700 99.7 Comparative Example 18 750 98.9 Comparative Example 20 3000 99.5
[0119] Combine Table 2 with Figure 4 It can be seen that Example 1 has higher half-cell cycle number and coulombic efficiency than other comparative examples, indicating that the ionic liquid electrolyte of Example 1 can well promote the uniform deposition / stripping of zinc metal.
[0120] The electrolytes of Example 1, Comparative Example 18 and Comparative Example 19 and the iodine positive electrode were assembled into full batteries, and the charge and discharge performance tests were carried out. The results are as follows:
[0121] Table 3
[0122]
[0123] Combine Table 3 with Figure 8 It can be seen that the ionic liquid additive can activate the positive conversion of iodine and trigger the redox reaction of bromine through catalysis, thereby greatly improving the capacity of the whole battery; by comparing Example 1 and Comparative Example 19, it can be seen that the ionic liquid concentration of Example 1 can better activate the positive conversion of iodine, and can better chelate polyiodides / polybromides, inhibit their dissolution shuttling, and improve the battery cycle life.
[0124] In addition, after the electrolytes prepared in Example 1, Comparative Example 6, Comparative Example 18 and Comparative Example 20 were assembled into zinc-iodine full batteries, the cyclic voltammetry curves of each battery were integrated to obtain Figure 1 and Figure 2 It can be seen that Example 1 has more obvious three pairs of redox peaks and a smaller polarization voltage, which indicates that the electrolyte of Example 1 activates the positive electrode conversion reaction of the iodine positive electrode material well and has good reversibility;
[0125] Symmetrical batteries were assembled using the electrolytes prepared in Example 1, Comparative Example 6, Comparative Example 18, Comparative Example 19 and Comparative Example 20, and the time-voltage curves of the batteries were integrated to obtain Figure 3 , and then assembled into a half-cell and integrated the measured cycle number-Coulomb efficiency curve to obtain Figure 4,from Figure 3 and Figure 4 It can be analyzed that different concentrations of ionic liquids also have a certain effect on the cycle life of the battery. By comparison, it can be seen that Example 1 is preferred, and the ionic liquid electrolyte of Example 1 can better promote the uniform deposition / stripping of zinc metal;
[0126] After the electrolyte prepared in Example 1 was used to assemble a symmetrical battery, after 100 cycles, the metal negative electrode was taken for analysis to obtain a scanning electron microscope photo of the metal negative electrode. Figure 5 and X X-ray diffraction pattern Figure 6 , combined with Figure 5 and Figure 6 It can be seen that the electrolyte prepared in Example 1 of the present invention can not only inhibit the growth of dendrites but also induce the Zn (101) crystal plane;
[0127] After assembling a full battery with the electrolyte prepared in Example 1, Comparative Example 18 and Comparative Example 19 and the iodine positive electrode and conducting cycle and charge-discharge performance tests, the results are as follows: Figure 7 Cycle curve and Figure 8 The charge and discharge curves of Figure 7 It can be seen that the zinc-iodine full battery prepared in Example 1 has the best cycle stability and the highest capacity; Figure 8 It can be seen that Example 1 has the best effect in activating the iodine positive conversion reaction through catalysis;
[0128] The zinc-iodine full battery was assembled with the electrolyte prepared in Example 1 and the rate performance was tested to obtain the rate performance curve Fig. 9 ,analyze Fig. 9 It can be found that the zinc-iodine full battery of Example 1 has good rate performance, which further illustrates that the prepared electrolyte can well chelate the dissolution shuttle of polyiodide / bromide;
[0129] The low N / P ratio zinc-iodine full battery curve assembled from the electrolyte prepared in Example 1 was measured to obtain Fig.10 ,from Fig.10 It can be seen that the full battery assembled with the electrolyte prepared in Example 1 is a full battery with high surface capacity and low N / P ratio.
[0130] Combination Figure 1-Figure 10 , Table 1-Table 3, Example 1-Example 4 and Comparative Example 1-Comparative Example 20, it can be seen that the electrolyte prepared by the present invention has better electrochemical performance.
[0131] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0132] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An electrolyte for improving the performance of a zinc-halogen battery, characterized in that: Includes ionic liquid, zinc salt and deionized water.
2. The electrolyte for improving the performance of zinc-halogen batteries according to claim 1, characterized in that: The ionic liquid is any one of 1-ethyl-3-methylimidazolium bromide, 1-propyl-3-methylimidazolium bromide and 1-butyl-3-methylimidazolium bromide.
3. The electrolyte for improving the performance of zinc-halogen batteries according to claim 1, characterized in that: The ionic liquid is 1-propyl-3-methylimidazolium bromide.
4. The electrolyte for improving the performance of zinc-halogen batteries according to claim 1, characterized in that: The zinc salt is any one of zinc trifluoromethanesulfonate, zinc sulfate heptahydrate, zinc chloride, zinc acetate, zinc tetrafluoroborate, and zinc perchlorate hexahydrate.
5. The electrolyte for improving the performance of zinc-halogen batteries according to claim 1, characterized in that: The zinc salt is zinc trifluoromethanesulfonate.
6. A method for preparing an electrolyte for improving the performance of a zinc-halogen battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1. First, add zinc salt to deionized water and stir to obtain a reference electrolyte; Step S2. Add ionic liquid to the reference electrolyte and stir to obtain an electrolyte that improves the performance of the zinc-halogen battery.
7. The method for preparing an electrolyte for improving the performance of a zinc-halogen battery according to claim 6, characterized in that: The mass ratio of the zinc salt to the deionized water in step S1 is 11-22:10-20.
8. The method for preparing an electrolyte for improving the performance of a zinc-halogen battery according to claim 6, characterized in that: The stirring time in step S1 is 10-20 minutes.
9. The method for preparing an electrolyte for improving the performance of a zinc-halogen battery according to claim 6, characterized in that: The mass ratio of the reference electrolyte to the ionic liquid in step S2 is 21-22:4-17.
10. The method for preparing an electrolyte for improving the performance of a zinc-halogen battery according to claim 6, characterized in that: The stirring time in step S2 is 24-25 hours.
Citation Information
Cited By
High-stability aqueous ion battery electrolyte with dynamic liquid crystal protection and application thereof
CN121076275A
